Environmental education and the learning of ill-defined concepts: The case of biodiversity - Daan van Weelie; Arjen E.J. Wals (Environmental Association of Southern Africa, 1997)
Sponsored by the Dutch Ministry of Agriculture, Nature Management and Fisheries, Wageningen Agricultural University and the University of Utrecht jointly investigated the diversity of meanings, values and uses of biodiversity in order to tap its educational potential more fully. Some of the research questions were: What does biodiversity mean? Does it mean the same to everybody? What are some underlying assumptions, values and ethics? What are the possibilities and limitations of the theme of biodiversity in educational settings? How can the theme become existentially relevant to the everyday life of citizens? What should the role of education be in this regard? The answers to these and other questions are to result in a blueprint for designing diverse teaching materials and learning activities. This contribution outlines the research, some preliminary findings and elements of the blueprint. The notion of conceptual ill-definedness is introduced. People from diverse backgrounds talk about biodiversity. Politicians, environmental activists, conservationists, agronomists, foresters, plant and animal taxonomists, geneticists, bio-geographers and ecologists, they all have absorbed and adapted the word biodiversity and talk to each other and to the public, albeit in different languages. All use biodiversity as the hot word in today's small talk, the fashionable keyword to an eloquent but superficial conversation, a worthy successor of earlier panaceas such as ecology, environmental quality, sustainable use or global change. (Vander Maarel, 1997:3)